The Importance of Patient Rights in Medical Experiments (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article is devoted to the protection of patient rights during medical experiments. The need to develop the Law of the Republic of Uzbekistan "On Biomedical Research" is noted, with the inclusion of provisions on the protection of the rights and dignity of people who participate in biomedical research as subjects. Accordingly, this should be reflected in the educational process when teaching the subject of "Bioethics". In the future, in accordance with the Constitution of the country, state guarantees for the protection of human rights, dignity, autonomy and integrity during biomedical research should be ensured by a national law developed on the basis of the model Law of the Interparliamentary Assembly of the CIS States.